Jules or Jim: Alternative Conformity to Minority Logics - Durand, Rodolphe; Jourdan, Julien (Academy of Management Journal, 2012)
To what extent do organizations respond favorably to minority participation—that is, conform to demands from minority resource suppliers that hold an unconventional logic? A favorable response to minority participation (i.e., “alternative conformity”) helps decrease the influence of dominant players, alter the resource suppliers' social structure, and promote new logics, which makes alternative conformity a “soft control strategy” for organizations. We expect a positive relationship between minority participation and alternative conformity and expect that relationship to be attenuated by organizations' adherence to a dominant logic, the centrality of minority logic holders, and a minority logic's institutional credit. We test and find strong support for our hypotheses using original data on investment funds in the French film industry (1994–2008).